Drug Inventory System Using Visual Basic.Net at Winni Farma Pharmacy - Yolla Krismonika; Indra Kanedi; Ricky Zulfiandry (Jurnal Komputer, Informasi dan Teknologi, 2021)
Winni Farma pharmacy is one of the pharmacies whose drug inventory data processing still uses the conventional system, where inventory management activities are still carried out manually which are recapitulated every month. The process of recording transaction data reports on the sale of incoming goods, outgoing goods and orders that are still using Microsoft Excel. By using Microsoft Excel, many obstacles are found that cause the work process to be ineffective and efficient. To overcome this problem, a drug inventory system program was created at the Winni Farma Pharmacy. With the aim that the management of drug inventory management is more accurate, orderly and easier to search for drug stock data, while indirectly increasing work performance and effectiveness at the Winni Farma Pharmacy. The research method that the researcher uses in making this application is from a manual or conventional system to a system development (electronic system) using the waterfall model. The waterfall system development method is a sequence of activities or activities carried out in system development starting from problem determination, actual system analysis, new system analysis, design, system implementation and testing. The software used in making this application is using Visual Basic.Net application. and supported by a Microsoft Access database with the results obtained in accordance with expectations and the use of the program has been implemented.